Concurrent Validity of Movement Screening Criteria Designed to Identify Injury Risk Factors in Adolescent Female Volleyball Players - Sophia Ulman; Sophia Ulman; Ashley Erdman; Alex Loewen; Michael Dressing; Charles Wyatt; Charles Wyatt; Gretchen Oliver; Lauren Butler; Dai Sugimoto; Dai Sugimoto; Amanda M. Black; et al. (Frontiers Media S.A., 2022)
Anterior cruciate ligament (ACL) injuries in female adolescent athletes occur at disproportionately high levels compared to their male counterparts. However, limited prospective data exist on the validity of low-cost screening tools that can proactively identify ACL injury risk, specifically for female athletes. The purpose of this study was to assess the concurrent validity of a three-task injury risk factor assessment by comparing visually derived outcome scores from two-dimensional (2D) video data with dichotomized three-dimensional (3D) biomechanical variables collected using motion capture technology. A total of 41 female club volleyball athletes (14.7 ± 1.4 years) were tested and asked to perform three tasks: double-leg vertical jump (DLVJ), single-leg squat (SLS), and single-leg drop landing (SLDL). One rater was trained on the scoring criteria for the 2D data and independently scored one forward-facing and one side-facing video for each task. Risk factors identified included poor knee position, lateral trunk lean, and excessive trunk flexion/extension. In addition, 3D joint angles were calculated for the trunk and knee in the sagittal and frontal planes and converted to dichotomous variables based on biomechanical thresholds of injury risk. For comparison of 2D and 3D outcomes, percent agreement and Cohen's kappa were calculated for each risk factor individually. Overall, 2D scores were found to exhibit moderate to excellent percent agreement with 3D outcomes for trunk position (69.1-97.1%). Specifically, ipsilateral trunk lean during single-leg tasks exhibited the highest agreement (85.3-88.2%) with moderate reliability (κ = 0.452-0.465). In addition, moderate to substantial reliability was found for trunk flexion during double-leg tasks (κ = 0.521-0.653); however, an evaluation of single-leg tasks resulted in only fair reliability (κ = 0.354). Furthermore, 2D scores were not successful in identifying poor knee position as percent agreement fell below 50% for both the single-leg tasks and averaged 60% agreement across both the phases of the DLVJ. Kappa coefficients further emphasized these trends indicating no to slight concurrent validity (κ = −0.047-0.167) across tasks. Overall, these findings emphasize the potential for valid, low-cost screening tools that can identify high-risk movement patterns. Further study is needed to develop improved assessment guidelines that may be employed through visual assessment in sports environments.